Electron transfer behavior of monolayer protected nanoclusters and nanowires of silver and gold - Sharma, Jadab; Vivek, J. P.; Vijayamohanan, Kunjukrishna P. (Journal of Nanoscience and Nanotechnology, 2006)
Understanding the electron transfer behavior of nanometer sized, both metallic and semiconducting particles and wires is important due to the fundamental interest in size and shape dependent electronic properties and also because of its applications in nano-electronic devices like single electron transistors and molecular switches. Monolayer protected nanoclusters enable one simple and elegant method of synthesis of these types of metallic and semiconducting materials using interfacial chemistry as has been successfully used in several applications ranging from catalysis to molecular electronics. The success of this type of nanostructured materials is due in part to the well known protecting/stabilizing action of the ligands (also known as surface passivating/capping agents), which facilitate the synthesis and processing of these hydrophobic colloids in solution form. The present article discusses the electron transfer behavior of silver nanowires and nanoparticles with varied sizes. In particular, we have investigated the electrochemical properties of silver nanowires (diameter 70 nm, length several micrometers) and compared with the behavior of similar relatively larger sized nanoparticles (size 40 nm). A critical analysis of the redox behavior of silver nanowires and nanoparticles is presented in aqueous medium under various electrolytic conditions along with a comparison of analogous properties of smaller sized (2-7 nm) silver and gold nanoclusters.
Keywords: cyclic voltammetry; nanoclusters/nanoparticles; Nanowires

Organic dye molecules as reducing agent for the synthesis of electroactive gold nanoplates - Sharma, Jadab; Vijayamohanan, Kunjukrishna P. (Journal of Colloid and Interface Science, 2006)
Highly crystalline, hexagonal and triangular nanoplates of gold are synthesized in high yield by a new wet chemical method using multifunctional molecules. Bismarck brown R (BBR) and Bismarck brown Y (BBY). This method involves a simple approach by keeping a mixture of aqueous HAuCl(4) solution and BBR/BBY solution in presence of poly(vinyl pyrrolidone) for 24 h. These nanostructures show unprecedented electrochemical properties exhibiting Surface confinement effect. The UV-visible (UV-vis) spectrum shows certain distinct features with absorptions at 300, 400,and 650 nm extending up to the near infrared region. Selected area electron diffraction patterns of these nanoparticles show highly oriented (111) crystal facets. X-ray diffraction analysis also confirms the Predominant orientation in the (111) crystal planes with lattice constant similar to 4.07 angstrom of face-centered-cubic (fcc) gold. X-ray photoelectron (XP) and Fourier transform infrared (FTIR) spectroscopic analysis shows the presence of a fraction of reducing molecules as surface passivating agent either in the unreacted molecular state or as a mixture of reacted and unreacted product which probably undergoes charge transfer with gold nanocrystals giving absorption at similar to 300 nm. (c) 2005 Elsevier Inc. All rights reserved.
Keywords: Bismarck brown; cyclic voltammetry; gold nanoplates; poly(vinyl pyrrolidone); surface plasmon resonance